Strategy of rotational atherectomy guided by optical coherence tomography - Bulak, Luiza; Zimoch, Wojciech J.; Rakotoarison, Oscar; Protasiewicz, Marcin; Reczuch, Krzysztof; Kübler, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
We present a case of a 70-year-old man with a medical history of exacerbated coronary artery disease, arterial hypertension, diabetes mellitus and hypercholesterolemia. After diagnostic coronary angiography the patient was qualified to undergo angioplasty of significant calcified stenosis in the right coronary artery (RCA). The distal RCA lesion was successfully predilated, but predilatations of the medial and proximal parts of the RCA at maximal pressure of 18 atm did not bring the expected result. Due to the undilatable character of the lesion rotational atherectomy (RA) was applied with several runs of the 1.5 mm burr. Unfortunately, the 3.5 × 20 mm non-compliant (NC) balloon was not fully opened again. The next step was the use of a 1.75 mm burr, but at this point the visualisation of the artery using optical coherence tomography (OCT) was introduced. Unexpectedly, OCT revealed highly calcified lesions with extensive dissection in the proximal RCA (Figures 1 A, B) which were not clearly visible in angiography.